Effect of Cascade Surface Roughness on Boundary Layer Flow Under Variable Conditions - Liu, C.; Li, Y.; Zhou, Z.; Wiśniewski, P. (Frontiers in Energy Research, 2022)
Under the influence of many factors, the surface roughness of the cascade will change during turbomachinery operation, which will affect the boundary layer flow of the cascade. In this article, the effects of cascade surface roughness on boundary layer flow under variable conditions are analyzed by experiments and numerical simulation. The results show that with the increase of roughness, the total pressure loss coefficient of the cascade decreases first and then increases. The larger the Reynolds number is, the greater the total pressure loss coefficient is, and the sensitive area of loss change is changed. In the sensitive area, the roughness has a greater influence on cascade loss. There are separation bubbles at the suction front edge of smooth cascades. With the increase of roughness, the degree of turbulence increases, and the transition process is accelerated. When the roughness is between 74 and 150 μm, the separation bubble disappears and the separation loss decreases. In conclusion, the aerodynamic loss of the cascade increases with the increase of roughness, and the cascade efficiency decreases. However, roughness can restrain the flow separation and reduce the separation loss. The two have gone through a process of one and the other. When the roughness is 74 μm, the displacement thickness, momentum thickness, and shape factor at the back of the cascade are the minimum.